2012
DOI: 10.1111/j.1574-6976.2011.00312.x
|View full text |Cite
|
Sign up to set email alerts
|

Ecology ofBorrelia burgdorferi sensu latoin Europe: transmission dynamics in multi-host systems, influence of molecular processes and effects of climate change

Abstract: The analysis of different multi-host systems suggests that even hosts that are not capable of transmitting Borrelia burgdorferi sensu lato (s.l.) to the tick vector, Ixodes ricinus, or that are secondary reservoirs for these agents contribute to the intensity of transmission and to the overall risk of Lyme borreliosis, through the process of vector augmentation and pathogen amplification. On the other hand, above certain threshold densities, or in the presence of competition with primary reservoir hosts or low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
161
3
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(178 citation statements)
references
References 156 publications
4
161
3
6
Order By: Relevance
“…To our knowledge, this review is the first to quantify the relative importance of host species for the different stages of I. ricinus, and our calculations support the widely held idea that small rodents are the most important hosts in feeding larval I. ricinus, that birds and rodents feed most of the nymphs, and that ungulates are the main hosts for adult I. ricinus 36,62 . We found that rodents and thrushes contribute most to the pool of B. burgdorferi infected nymphs.…”
Section: Resultssupporting
confidence: 61%
See 2 more Smart Citations
“…To our knowledge, this review is the first to quantify the relative importance of host species for the different stages of I. ricinus, and our calculations support the widely held idea that small rodents are the most important hosts in feeding larval I. ricinus, that birds and rodents feed most of the nymphs, and that ungulates are the main hosts for adult I. ricinus 36,62 . We found that rodents and thrushes contribute most to the pool of B. burgdorferi infected nymphs.…”
Section: Resultssupporting
confidence: 61%
“…Both in Europe and in North America, I. ricinus and I. scapularis populations have spread and increased in density in recent decades, most probably due to a multitude of man-made changes to the environment, which has resulted in an increase in Lyme disease incidence 49,61 . Lyme disease risk is determined by multiple biological, environmental and societal factors 8,62,63 . These can be split into two distinct groups, 1) factors determining the number of questing Ixodes ticks infected with B. burgdorferi, and 2) factors determining the level of human exposure to ticks 39 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…El mantenimiento de B. burgdorferi s.l., así como de otros agentes patógenos zoonóticos transmitidos por garrapatas, depende de la abundancia de los reservorios y vectores competentes, y de la interacción entre huésped y vector, por lo cual la relación entre garrapatas del género Ixodes, la espiroqueta y los mamíferos huésped ha sido objeto de numerosos estudios (12,13). En Europa y Estados Unidos se han detectado muchas especies de mamíferos como reservorios competentes, pero a los roedores se los ha implicado como los principales reservorios naturales de B. burgdorferi s.l.…”
unclassified
“…lack genes involved in the biosynthesis of amino acids, fatty acids, and nucleotides pointing to the need of getting additional nutrients from their different hosts (8). These molecules must be taken up from the vertebrate hosts including birds or the invertebrate tick vector (9,10). The first step in nutrient uptake in Gram-negative bacteria is accomplished by porins.…”
mentioning
confidence: 99%